EFEITOS DA ADIÇÃO DE NANOTUBOS DE CARBONO E C-S-H PRECIPITADO NAS PROPRIEDADES DE NANOCOMPÓSITOS CIMENTÍCIOS - Duart, Marcelo Adriano (2017)
Civil construction industry has been developing technologically with the growth in the number of works in various sectors such as housing, transport, industry and infrastructure. This study is intended to contribute to the development of scientific cementitious materials by studying the use of carbon nanomaterials as carbon nanotubes (CNT) and nanoparticles of Hydrated Calcium Silicate (C-S-H) incorporated into the matrix of these materials, which can be categorized as composite, in this case nanocomposites. Materials performance is usually related to the existence of considerable flaws or deficiencies in some properties or characteristics. The incorporation of nanomaterials is a possibility for the amelioration or even create some characteristic and materials property. The use of CNT has already been investigated and the results have shown that though with increase of costs produced materials have positive characteristics such compression and tensile resistance increase and still elasticity modulus increase. Currently steel is used but the fibers and filler materials such as CNT may be an alternative because they can have tensile strength up to 100 times higher than steel, as recent research has shown. The main assumption is that nanoparticles such as C-S-H and oxidized multi walled carbon nanotubes (MWCNT-OX) favor the kinetics of cement hydration and contribute to the nucleation and crystal growth enhancing material characteristics produced as concrete and mortar, for example. In general, it was verified that the combined additions of C-S-H with Ca / Si = 0.8 ratio with nanotubes brought positive results of nanocomposite nanostructure improvements, verified by porosity, permeability analysis and qualitative analysis of electron microscopy images. An increase in the value of the mechanical properties analyzed was shown as a 33% increase in compressive strength, 38% increase in modulus of elasticity and 30% in tensile strength. It is also concluded that using the C-S-H addition with Ca/Si ratio = 0.8 in isolation is a viable alternative to produce relevant results with a lower cost than to opt for mixed additions, since CNT are still materials with high cost and more complex production than C-S-H.